Wczesna inicjacja seksualna młodzieży – przyczyny i konsekwencje - Jankowiak, Barbara; Gulczyńska, Anna (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
Juvenescence constitutes period between infantile sexuality and sexuality of young man. Adolescence is time of discovering sexual identity, initiating new sexual behaviors and involving into intimate relationships. During this period, the forms of sexual activity are developing from less to more and more mature – from masturbation, through petting to sexual initiation. Decision of a first sexual intercourse is an important act for every person. Nevertheless, sexual initiation which is precocious, in a stage of unformed identity, can disturb psychosexual functioning of an individual causing unplanned pregnancies, leading to sexually transmissible diseases and initiating risky sexual behaviors. The causes of starting precocious sexual activity are associated with improper models of upbringing (strictness or lack of interference) as well as with distancing of youth from pedagogical or educational influences of school or church. These traditional socializing agendas are replaced with media influences and behavior patterns providing by peers. It seems that only complex acts from pedagogical and socializing backgrounds can contribute starting responsible behaviors of youth in sexual field.
On Youth’s Early Sexual Initiation – Causes and Consequences
Keywords: sexual initiation; causes and consequences of sexual initiation; youth